The Influence of Climate Change on Migration Patterns, Displacement, and Food Insecurity in KwaZulu-Natal - Koswana, Victor (African Journal of Governance and Development, 2025)
Climate change, displacement, migration, and food insecurity have been among the most pressing and interconnected challenges that Africa has faced over the past few years. Even South Africa itself has been on the receiving end of the aggravating effects of climate variability, in the form of intense weather patterns, including brutal floods and, at times, snow. These climatic shocks not only pose a threat to livelihoods and infrastructure but also lead to internal displacement and heightened food insecurity. South Africa's hunger, rising food insecurity, poverty, and socio-economic issues received a significant unintended natural cause in this tragedy, without preparedness for adaptation, resilience, and development. Increased disaster preparedness, climate adaptation, and mitigation efforts are needed for the South African scenario. The frequency and magnitude of these events underscore the population's susceptibility and the importance of collective action in developing resilience in South Africa. The response to such intricacies requires concerted efforts in coping with both environmental and socioeconomic determinants. The study uses secondary data analysis to explore the research questions and argues that climate change is accelerating human displacement, internal migration, and food insecurity. This investigation concludes that supportive policy strategies should be implemented to assist vulnerable communities, as recurring floods continue to pose a significant challenge during the rainy seasons in the KwaZulu-Natal and Eastern Cape provinces. Furthermore, it provides recommendations to policymakers on climate change adaptation and strengthening resilience efforts, ensuring better preparedness for future disasters.